Analysis of Caesarean Section Rates and Source of Payment Using the Robson Classification System - Nurhayati, Fitasari Nidia; Prasetyo, Budi; Miftahussurur, Muhammad (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Sectio caesarea delivery is the last alternative to save the mother and fetus when normal delivery is not possible. The increase in caesarean section worldwide has become a major public health problem, so it is necessary to supervise to reduce the number of caesarean sections that are considered unnecessary, one of which is through the Robson Classification. The existence of health insurance for the people of Indonesia, including BPJS which covers the costs of sectio caesarea, makes it possible to increase the incidence of sectio caesarea. The aim of the study was to analyze the incidence of sectio caesarea and financing status based on Robson's classification at Muhammadiyah Babat Hospital. Subjects and Method: This study used a retrospective observational analytic method with a cross sectional design. The research sample was mothers giving birth at Muhammadiyah Babat Hospital who were included in the inclusion criteria and were taken through a total sampling technique of 127 mothers giving birth. The dependent variable is sectio caesarea. The independent variable is financing status. The instrument used was medical record data collected in collection sheets and analyzed using the Chi Square test. Results: A total of 87 (68.5%) subjects gave birth by sectio caesarea with the prevalence of the Robson group 2, 4, and 5 as the main contributor. A total of 64 (63.4%) subjects gave birth by sectio caesarea with BPJS financing status. The results of the chi-square analysis showed that mothers with BPJS financing status reduced the incidence of sectio caesarea, and it was statistically significant (OR= 0.23; 95% CI= 0.06 to 0.80; p= 0.026). Conclusion: The data shows that the incidence of sectio caesarea is still very high and most are in the Robson group 1-5 with BPJS financing status. Based on Robson's grouping results, there is a relationship between financing status and the incidence of sectio caesarea, BPJS financing status reduces the incidence of caesarean section. Keywords: sectio caesarea, robson classification, financing status. Correspondence: Budi Prasetyo. Department of Obstetrics and Gynecology, Facullty of Medicine, Universitas Airlangga, Indonesia, Jl. Mayjen Pro. Dr. Moestopo No. 47, Pacar Kembang, Tambaksari, Surabaya 60132, East Java, Indonesia. Email: budi-p@fk.unair.ac.id. Mobile: +6281553019486